Developments in silicone technology for use in stoma care. (26th March 2020) - Swift, Thomas; Westgate, Gillian; Van Onselen, Julie; Lee, Stewart
Abstract : Soft silicone's flexibility, adhesive capacity and non-toxic, non-odourous and hypoallergenic nature have made it an established material for adhesive and protective therapeutic devices. In wound care, silicone is a component of contact layer dressings for superficial wounds and silicone gel sheeting for reducing the risk of scarring, as well as of barriers for incontinence-associated dermatitis. Regarding stoma accessories, silicone is established in barrier films to prevent contact dermatitis, adhesive removers to prevent skin stripping and filler gels to prevent appliance leaks. Until recently, silicone has not been used in stoma appliances flanges, as its hydrophobic nature has not allowed for moisture management to permit trans-epidermal water loss and prevent maceration. Traditional hydrocolloid appliances manage moisture by absorbing water, but this can lead to saturation and moisture-associated skin damage (MASD), as well as increased adhesion and resultant skin tears on removal, known as medical adhesive-related skin injury (MARSI). However, novel silicone compounds have been developed with a distinct evaporation-based mechanism of moisture management. This uses colloidal separation to allow the passage of water vapour at a rate equivalent to normal trans-epidermal water loss. It has been shown to minimise MASD, increase wear time and permit atraumatic removal without the use of adhesive solvents. Trio Healthcare has introduced this technology with a range of silicone-based flange extenders and is working with the University of Bradford Centre for Skin Sciences on prototype silicone-based stoma appliance flanges designed to significantly reduce the incidence of peristomal skin complications, such as MARSI and MASD. It is hoped that this will also increase appliance wear time, reduce costs and improve patient quality of life.